An interpretation of symbols in Ade Firza Paloh's Bunga Di Telinga / Siti Zarikh Sofiah Abu Bakar - Abu Bakar, Siti Zarikh Sofiah (Universiti Teknologi MARA Cawangan Kedah, 2020)
Figurative language always has a special place in the heart of literature enthusiasts. This is because; it plays a vital role in beautifying the literary works as well as conveying its figurative meaning which could lead to ambiguity thus resulting in various interpretations (Fadaee, 2010). One of the frequent used figurative languages in literature is symbolism. Flower behind the ear is the prominent symbol offered by Ade Firza Paloh in the lyrics of Bunga di Telinga. Thus, this study investigates the differences in the interpretation of the symbols presented and the difficulty level rated by the respondents of different literature background. In reference to literature background, purposive sampling is applied in this study. The study involved LG120 (Diploma in English for Professional Communication) students from UiTM (Universiti Teknologi MARA) Cawangan Johor; two groups (Semester 1 and Semester 2). A mixed-method sequential explanatory study involved an experimental design and a semi-structured interview procedure. Data analysis will make use of the t-test procedure for the statistical results of the quantitative data, and the thematic analysis for qualitative data obtained. In contrast to previous literatures, there is no significant difference shown by the interpretation and difficulty level rating obtained from the two groups studied.